Feedback-controlled running holograms in strongly absorbing photorefractive materials - Frejlich, J.; Freschi, A. A. [UNESP]; Garcia, P. M.; Shamonina, E.; Gayvoronsky, V. Ya; Ringhofer, K. H. (Optica Publishing Group, 2000)
We propose a mathematical model for the movement in absorbing materials of photorefractive holograms under feedback constraints. We use this model to analyze the speed of a fringe-locked running hologram in photorefractive sillenite crystals that usually exhibit a strong absorption effect. Fringe-locked experiments permit us to compute the quantum efficiency for the photogeneration of charge carriers in photorefractive crystals if the effect of bulk absorption and the effective value of the externally applied field are adequately taken into consideration. A Bi12TiO20 sample was measured with the 532-nm laser wavelength, and a quantum efficiency of φ = 0.37 was obtained. Disregarding absorption leads to large errors in φ. © 2000 Optical Society of America.
Keywords: Feedback control; Light absorption; Photorefractive materials; Quantum efficiency; Photogeneration; Holograms